(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The worldwide incidence of abnormally invasive placenta is rapidly rising, following the trend of increasing cesarean delivery. It is a heterogeneous condition and has a high maternal morbidity and mortality rate, presenting specific intrapartum challenges. The presence of a previous uterine scar is a strong risk factor for developing abnormally invasive placentation (AIP).